Synthesis and In Vitro and In Vivo Evaluation of a New 68Ga-Semicarbazone Complex: Potential PET Radiopharmaceutical for Tumor Imaging - N. S. Al-Hokbany; Basim Alotaibi; Suad Bin Amer; Subhani M. Okarvi; Ibrahim Al-Jammaz (Journal of Chemistry)
In an attempt to develop new tumor imaging radiotracers with favorable biochemical properties, we have synthesized new 68Ga-2-acetylpyridine semicarbazone (68Ga-[APSC]2) as a potential positron emission tomography (PET) tumor imaging agent using a straightforward and a one-step simple reaction. Radiochemical yield and purity were quantitative without HPLC purification. Biodistribution studies in nude mice model bearing human MDA-MB-231 cell line xenografts displayed significant tumor uptake of 68Ga-[APSC]2 radiotracer after 2 h postinjection (p.i.). The initial results demonstrate that 68Ga-[APSC]2 radiotracer may be useful probe for detecting and staging of hypoxic tumor using PET imaging modality.